Three-Dimensional Printing in Minimally Invasive Cardiac Surgery: Optimizing Surgical Planning and Education with Life-Like Models - Montanhesi,Paola Keese (2022)
Abstract Over recent years, the surgical community has demonstrated a growing interest in imaging advancements that enable more detailed and accurate preoperative diagnoses. Alongside with traditional imaging methods, three-dimensional (3-D) printing emerged as an attractive tool to complement pathology assessment and surgical planning. Minimally invasive cardiac surgery, with its wide range of challenging procedures and innovative techniques, represents an ideal territory for testing its precision, efficacy, and clinical impact. This review summarizes the available literature on 3-D printing usefulness in minimally invasive cardiac surgery, illustrated with images from a selected surgical case. As data collected demonstrates, life-like models may be a valuable adjunct tool in surgical learning, preoperative planning, and simulation, potentially adding safety to the procedure and contributing to better outcomes.